2012
DOI: 10.15261/serdj.19.137
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Limonin from Orange (<i>Citrus reticulata</i> Blanco) Seeds by the Flash Extraction Method

Abstract: A flash extraction method was investigated for mass production of limonin from orange (Citrus reticulata Blanco) seeds. The limonin was extracted by using flash extraction for 2 min. The extraction conditions optimized by response surface methodology were as follows: ethanol concentration, 72% (v/v); solvent/solid ratio, 29:1 mL/g; rotational speed, 4000 r/min. The limonin was crystallized from the mixed solution of dichloromethane and isopropanol (1:3) at 4 o C for 1 h. The limonin crystals were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The extraction yield by Soxhlet method was 49.6 , therefore, the extraction rate by flash extraction reached 99.4 . The flash extraction time of 2 min is in accordance with the previous study on the mass production of limonin from orange seeds 14 . The advantage of flash extraction is rapid and efficient that the extraction time is extremely short and generally less than 3 min.…”
Section: Effects Of Ash Extraction Parameters On Oil Yieldsupporting
confidence: 78%
See 3 more Smart Citations
“…The extraction yield by Soxhlet method was 49.6 , therefore, the extraction rate by flash extraction reached 99.4 . The flash extraction time of 2 min is in accordance with the previous study on the mass production of limonin from orange seeds 14 . The advantage of flash extraction is rapid and efficient that the extraction time is extremely short and generally less than 3 min.…”
Section: Effects Of Ash Extraction Parameters On Oil Yieldsupporting
confidence: 78%
“…This apparatus was developed by Liu et al and is composed of a high-speed 4000 g two-layer cutter head with gap of 0.3 mm 14 . The single factor study was carried out as one factor was changed while the others kept stable in each experiment.…”
Section: Oil Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The F-value (13.3) of the regression model (p < 0.01) showed a high significance, confirming the adequacy of the quadratic model. The high value of the determination coefficient R 2 (0.9447) demonstrated that the model adequately represented a real relationship between the independent variables, which showed that 94% of the variation in the response could be explained by the model [25]. The p-value for the lack of fit (0.442) implied that the lack of fit was not significant compared to the pure error.…”
Section: Regression Analysismentioning
confidence: 95%